Teamwork in the NICU Setting and Its Association with Health Care–Associated Infections in Very Low-Birth-Weight Infants - Profit, Jochen; Sharek, Paul J.; Kan, Peiyi; Rigdon, Joseph; Desai, Manisha; Nisbet, Courtney C.; Tawfik, Daniel S.; Thomas, Eric J.; Lee, Henry C.; Sexton, J. Bryan (American Journal of Perinatology, 2017)
Background and Objective Teamwork may affect clinical care in the neonatal intensive care unit (NICU) setting. The objective of this study was to assess teamwork climate across NICUs and to test scale-level and item-level associations with health care–associated infection (HAI) rates in very low-birth-weight (VLBW) infants.Methods Cross-sectional study of the association between HAI rates, defined as any bacterial or fungal infection during the birth hospitalization, among 6,663 VLBW infants cared for in 44 NICUs between 2010 and 2012. NICU HAI rates were correlated with teamwork climate ratings obtained in 2011 from 2,073 of 3,294 eligible NICU health professionals (response rate 63%). The relation between HAI rates and NICU teamwork climate was assessed using logistic regression models including NICU as a random effect.Results Across NICUs, 36 to 100% (mean 66%) of respondents reported good teamwork. HAI rates were significantly and independently associated with teamwork climate (odds ratio, 0.82; 95% confidence interval, 0.73–0.92, p = 0.005), such that the odds of an infant contracting a HAI decreased by 18% with each 10% rise in NICU respondents reporting good teamwork.Conclusion Improving teamwork may be an important element in infection control efforts.
Keywords: infant; newborn; teamwork; safety culture; neonatal intensive care unit; infection